2014
DOI: 10.5958/2231-6701.2014.01206.8
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall-Runoff Modeling Using MIKE 11 NAM Model for Vinayakpur Intercepted Catchment, Chhattisgarh

Abstract: Rainfall-runoff estimation for a catchment is of vital importance in most of the hydrologic analysis for water resources planning. This study envisages the rainfall-runoff modeling using MIKE 11 NAM model in Vinayakpur intercepted catchment in Chhattisgarh state. The model was calibrated using measured stream flow data for the period 2001 to 2004 and then validated from period 2005 to 2007. The calibration and validation procedures were carried out to provide a satisfactory estimation. The simulated runoff occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…The sensitivity analysis of Mike-11 NAM model parameters concluded that the maximum water content in surface storage ( U max ), the maximum water content in the lower zone/root zone ( L max ) and timing constant for base flow ( CK BF ) were the most significant Mike-11 NAM model parameters for daily runoff simulation in the catchment. The sensitivity analysis results were found analogous to a study made in the Vinayakpur catchment of Seonath sub-basin bySingh et al (2014). The rugged terrain upstream of the catchment governs the surface water storage, and dominant agricultural land use in the central part of the catchment affects the runoff generation in the catchment.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…The sensitivity analysis of Mike-11 NAM model parameters concluded that the maximum water content in surface storage ( U max ), the maximum water content in the lower zone/root zone ( L max ) and timing constant for base flow ( CK BF ) were the most significant Mike-11 NAM model parameters for daily runoff simulation in the catchment. The sensitivity analysis results were found analogous to a study made in the Vinayakpur catchment of Seonath sub-basin bySingh et al (2014). The rugged terrain upstream of the catchment governs the surface water storage, and dominant agricultural land use in the central part of the catchment affects the runoff generation in the catchment.…”
supporting
confidence: 63%
“…Mike-11 Nedbor Afstromnings model (NAM) is a theory-driven model that simulates the rainfall-runoff process at the catchment scale (Singh et al, 2014). Loliyana et al, (2015) applied the Mike-11 NAM model for Purna catchment in the Tapi basin and found it reasonably good in simulating annual hydrographs at daily time scales along with the prediction of water yield and flooding condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MIKEHydro Basin model for Sebwe catchment was manually calibrated. The Nedbor-Afstromnings Model (NAM) is a deterministic, conceptual rainfall-runoff, and lumped model, which means that the catchment is analyzed as a single unit with average values of parameters [35]. Owing to the lack of continuous discharge measurements of the Sebwe river, the NAM was adopted for the calibration process.…”
Section: Hydrological and Climate Data: Model Calibrationmentioning
confidence: 99%
“…Such models are constructed using empirically and/or physically based expressions of hydrological processes, e.g. infiltration, runoff yield, and influx processes (El Alfy, 2016; Jie et al, 2016; Oudin et al, 2006; Singh et al, 2014). However, the uncertainties associated with hydrological modelling should be considered, especially with respect to the inputs, parameters, model structure, and outputs (e.g.…”
Section: Introductionmentioning
confidence: 99%